Research handbook on transnational crime - Mitsilegas, Valsamis; Hufnagel, Saskia; Moiseienko, Anton (Research handbooks on globalisation and the law, 2019)
"The increasing prevalence of transnational crime in a mobile and interconnected world presents serious challenges, both in terms of analysing these issues and attempting to tackle and prevent them. This Research Handbook on Transnational Crime is an interdisciplinary, up-to-date guide to this growing field, written by an international cohort of leading scholars and experts. The multifaceted nature of the problem is reflected in the structure of this innovative Research Handbook, covering all the major areas of transnational crime, including terrorism, money laundering, environmental crime, migration-related crime, human trafficking, drug trafficking, cybercrime and heritage crime. Each sector is examined through three dedicated chapters that consider in turn legal responses to a given crime, its current criminological understanding, and the practical challenges of policing and prosecution, providing a well-rounded, detailed discussion of each topic. This timely Research Handbook also includes chapters focusing on responses to transnational crime in specific regions, including the EU, the African Union, Asia, South America and ex-Soviet Union countries. This Research Handbook will be crucial reading for academics and students with an interest in criminal justice and criminology, particularly those working on international and transnational crime. Policymakers and practitioners will also find its insights into practical challenges in the field invaluable"--